2022
DOI: 10.1097/inf.0000000000003736
|View full text |Cite
|
Sign up to set email alerts
|

Serratia Infection Epidemiology Among Very Preterm Infants in the Neonatal Intensive Care Unit

Abstract: Background: Serratia spp. are opportunistic, multidrug resistant, Gram-negative pathogens, previously described among preterm infants in case reports or outbreaks of infection. We describe Serratia late-onset infection (LOI) in very preterm infants in a large, contemporary, nationally representative cohort. Methods: In this secondary analysis of prospectively collected data of preterm infants born 401–1500 grams and/or 22–29 weeks gestational age from 2018 to 2020 at 774 Vermont Oxford Network members, LOI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…According to Canadian studies, the incidence of Serratia infections is estimated at 10.8 per 100,000 persons per year, with a hospital incidence rate of 0.4 per 1,000 hospitalized patients [ 13 ]. On the other hand, a multicenter study of premature infants in 774 hospitals in the United States showed an increased incidence of invasive Serratia, corresponding to approximately 2.3 Serratia infections per 1,000 premature infants [ 29 ]. Both studies showed a higher incidence than that found in our work.…”
Section: Discussionmentioning
confidence: 99%
“…According to Canadian studies, the incidence of Serratia infections is estimated at 10.8 per 100,000 persons per year, with a hospital incidence rate of 0.4 per 1,000 hospitalized patients [ 13 ]. On the other hand, a multicenter study of premature infants in 774 hospitals in the United States showed an increased incidence of invasive Serratia, corresponding to approximately 2.3 Serratia infections per 1,000 premature infants [ 29 ]. Both studies showed a higher incidence than that found in our work.…”
Section: Discussionmentioning
confidence: 99%
“…There have been outbreaks of Serratia marcescens in neonatal intensive care units described in the literature [ 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 23 ]. Still, they often did not progress to the central nervous system or other complications.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental sources have been described (e.g., contaminated medical devices, parenteral nutrition, contaminated milk, intravenous and topical solutions, liquid soap, respiratory care equipment, and air conditioning) [ 6 , 7 , 8 , 9 ]. Serratia can cause invasive systemic infections in newborns due to the immaturity of the immune system [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serratia marcescens is the most important opportunistic human pathogen among Serratia species, often multidrug resistant and involved in outbreaks of HAIs in neonatal intensive care units (NICU) (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). A recent study reported an incidence of 2.3 Serratia late-onset infections per 1,000 very preterm infants, associated with lower survival and significant morbidity (35). S. marcescens is the second most frequently cited species in studies linking sinks with bacterial HAI in NICU, preceded by Pseudomonas aeruginosa (20).…”
mentioning
confidence: 99%